Optimized scheduling of diesel - renewable systems with pumped hydro storage - Bokabo, B.; Kusakana, K. (IEEE Xplore: Industrial and Commercial Use of Energy (ICUE), 2016 International Conference, 2017)
The present paper develops a model to optimize the daily operation of a hybrid energy system consisting of a photovoltaic unit, a wind unit, a pumped hydro storage system and a diesel generator. The main purpose of the developed model is to minimize the hybrid system’s operation cost while optimizing the system’s power flow considering the different component’s operational constraints. The simulations have been performed using “fmincon” implemented in Matlab. The model has been applied to two test examples; the simulation results are analyzed and compared to the case where the diesel generator is used alone to supply the given load demand. The results show that using the developed control model, fuel saving can be achieved compared to the case where the diesel is used alone to supply the same load patters.
Published Conference Proceedings
Keywords: Renewable energy; Hybrid system; Pumped hydro storage; Optimal operation scheduling; Cost minimization